How populism and culture wars affect fundamental rights - Ferreira Dias, J. (Journal of Populism Studies, 2024)
This paper examines the intricate relationship between populism, culture wars, and fundamental rights. It explores how the rise of populist movements and the intensification of culture wars reshape the interpretation and implementation of fundamental rights, often polarizing societal values and threatening democratic principles. By delving into the mechanisms underlying these phenomena, the paper highlights how populism amplifies ideological divides, leveraging culture wars to contest principles of equality, freedom of expression, and social justice. The study categorizes populism into economic, political, and cultural strands, analyzing their combined effects with culture wars on the discourse and practices of democracy. Using examples such as the rollback of reproductive rights in the United States and the use of nationalist narratives in Brazil and India, the paper underscores the tangible consequences of these dynamics. This exploration reveals the challenges these contentious forces pose to the principles of democracy, human rights, and social cohesion, as well as their influence on competing democratic models: liberal, majoritarian, and minoritarian.